The Influence Loyalty on Repurchase Interest In Online Shopping At Shopee - Alya cahyani; Rima Hafidz Ramadhani; Rizaludin; Ahmad Nuh (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
Online shopping presents a different environment, atmosphere and experience compared to offline shopping because of the convenience provided when transacting at any location via the internet from a web browser or mobile application etc. This study aims to understand the influence of corporate responsibility, consumer trust, and consumer loyalty on repurchase interest in shopping applications in the digital era. This research involved 138 respondents who were active users of online shopping applications on the application (shoppee). The method used is quantitative using an online survey with a questionnaire designed to measure respondents' perceptions of corporate responsibility, consumer trust, consumer loyalty and repurchase interest. The collected data is then analyzed using appropriate statistical techniques to determine the relationship between these variables. The research method used is quantitative by means of an online survey, with an instrument in the form of a questionnaire that has been specifically designed to measure research variables. This questionnaire includes items designed to measure respondents' perceptions of corporate responsibility, consumer trust, consumer loyalty and repurchase intention. The data analysis carried out shows that responsibility, consumer trust and consumer loyalty have a positive effect on repurchase interest in the Shoppee application. These results indicate that shoppee applications that demonstrate high responsibility, build strong trust with their consumers, and are able to maintain consumer loyalty, tend to have consumers with higher repurchase interest. The results of this research provide important insights for shoppee applications operating in the digital era. By understanding the factors that influence repurchase interest, online shopping applications, namely shops, can design and implement more effective strategies to increase customer retention and long-term profitability.